Ultrastructural aspects of the retractor ocular bulbi muscle in the opossum (Didelphis albiventris) - Matheus, SMM; Soares, J. C. (Editrice Compositori Bologna, 1999)
In the present study the different types of muscle fibers of the retractor ocular bulbi muscle of the South American opossum were classified according to their ultrastructural characteristics. The tridimensional characteristics of the neuromuscular junctions present: in this muscle were also demonstrated by scanning electron microscopy (SEM). Five adult opossums, three males and two females, were perfused with fixative solution through the left ventricle and their right retractor ocular bulbi muscle was prepared for the ultrastructural study of muscle fibers. The contralateral muscle was used for the study of neuromuscular junctions by SEM. Three types of fibers were detected, denoted 1r, 2r and 3r. Only simple neuromuscular junctions of the plate type were visualized by SEM.
Keywords: retractor muscle; muscle fibers; neuromuscular junction; ultrastructure